MODERN DIAGNOSIS OF NEPHROBLASTOMA IN CHILDREN - Nishanov Doniyor Anorboyevich; Anorbaeva India Doniyorovna; Pulatov Khabibulla Khayrullayevich; Sobirova Dildora Ravshanovna; Matrasulov Roman Sobirovich (Journals Park Publishing, 2022)
Nephroblastoma is a highly malignant embryonic tumor originating from developing kidney tissues. The disease is the most common malignant neoplasm of the genitourinary tract in children. Most common before the age of 5 years with equal frequency in boys and girls, the relationship between maternal age and the likelihood of having a child with Wilms nephroblastoma is often associated with congenital anomalies.
Keywords: Nephroblastoma; malignant embryonic tumor; kidney tissues